Initial Experience of Self-Expanding Metal Ureteral Stent in Recurrent Ureteral Stricture After Ureteroplasty - Gao, Xiaoshuai; Chen, Jixiang; Jian, Zhongyu; Wang, Menghua; Wang, Wei; Peng, Liao; Liu, Zhenghuan; Wei, Xin (Frontiers in Surgery, 2021)
Background: The aim of this prospective study was to assess the safety and effectiveness of self-expanding metal ureteral stent (MUS) for the treatment of recurrent ureteral stricture after ureteroplasty. Methods: We prospectively included 24 patients who underwent MUS implantation between February 2019 and August 2020. The inclusion criteria for the procedure were recurrent ureteral strictures after ureteroplasty. A paired T test was used to compare continuous variables before and after surgery. Results: A total of 24 patients were finally included in this study. The stricture site was most common on the proximal ureter 19 (79.2%), followed by distal ureter 4 (16.7%) and middle ureter 1 (4.2%). The median length of ureteral stricture is 2.5 (range 1-18) cm. The median operative time was 51.5 minutes, and the median hospital stay time after surgery was 3 days. Postoperative complication included pain 1 (4.2%), urinary tract infection 2 (8.3%) and hematuria 2 (8.3%). After a median follow-up of 12 months, 19/24 (83.3%) patients were clinically and radiologically successful. We endoscopically adjusted or exchanged the failed stents. The volume of hydronephrosis (124.7±132.5 VS 66.4±73.2 cm3, P=0.015), blood creatinine level (104.5±45.4 VS 80.1±23.2 μmol/L, P=0.044) and urea nitrogen level (6.9±2.4 VS 4.8±1.5 mmol/L, P=0.003) decreased significantly after a median follow-up of 12 months. Conclusions: MUS is a safe and effective way to manage recurrent ureteral strictures after ureteroplasty. This technique provides a new choice for the treatment of recurrent stricture.